2016
DOI: 10.1242/jeb.132019
|View full text |Cite
|
Sign up to set email alerts
|

Salt preferences of honey bee water foragers

Abstract: The importance of dietary salt may explain why bees are often observed collecting brackish water, a habit that may expose them to harmful xenobiotics. However, the individual salt preferences of water-collecting bees were not known. We measured the proboscis extension reflex (PER) response of Apis mellifera water foragers to 0-10% w/w solutions of Na, Mg and K, ions that provide essential nutrients. We also tested phosphate, which can deter foraging. Bees exhibited significant preferences, with the most PER re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 43 publications
4
43
1
1
Order By: Relevance
“…Bees were not pre-fed water like in some other studies (e.g. Pankiw et al 2001 ) and some might have been thirsty as response levels came close to those found in water collecting foragers that were stimulated with pure water (around 30–60% PE, Lau and Nieh 2016 ). But importantly, we did not see an increase in response to sucrose in the control (S) group over time.…”
Section: Resultssupporting
confidence: 63%
“…Bees were not pre-fed water like in some other studies (e.g. Pankiw et al 2001 ) and some might have been thirsty as response levels came close to those found in water collecting foragers that were stimulated with pure water (around 30–60% PE, Lau and Nieh 2016 ). But importantly, we did not see an increase in response to sucrose in the control (S) group over time.…”
Section: Resultssupporting
confidence: 63%
“…This Na and K must be replenished. Solutions laced with Na are attractive to pollinators (Arms et al, ; Lau & Nieh, ), and floral nectars can vary 24‐fold in Na concentration within plant communities (Hiebert & Calder, ). We suggest the working hypothesis that gives Na a more functional role in plant community ecology, one in which the plants spike nectar and exudates with Na required to attract mutualists and deter enemies.…”
Section: Discussionmentioning
confidence: 99%
“…Even if 100% Na assimilation is considered, it is unlikely that bees concentrate the scarce Na available in pollen to a great extent, and nectar cannot serve as a source of nutritional elements other than C. Thus, it is likely that the bees supplement Na from sources other than pollen and nectar. For bees, the source of non-C elements may be “dirty water”, as honeybees are known to willingly utilize liquid waste and “dirty water”, which are rich in decomposing matter and salts [ 89 , 90 ]. We hypothesize that bees are able to produce stoichiometrically balanced jelly for the reared larvae by supplementing Na deficiencies with “dirty water”.…”
Section: Discussionmentioning
confidence: 99%